2009
DOI: 10.1002/ijc.24421
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid consumption and esophageal cancer among black and white men in the United States

Abstract: Flavonoids and proanthocyanidins are bioactive polyphenolic components of fruits and vegetables that may account for part of the protective effect of raw fruit and vegetable consumption in esophageal cancer. We studied the relationship between esophageal cancer and dietary proanthocyanidins, flavonoids and flavonoid subclasses (anthocyanidins, flavan-3-ols, flavanones, flavones, flavonols and isoflavonoids) using recently developed USDA and Tufts flavonoid and proanthocyanidin databases. The study was a popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…In particular, flavonones associate with lower risk of esophageal squamous cell carcinoma (3), flavones and flavonols against renal cell carcinoma (4), and increased intakes of anthocyanadins, flavones, and flavonols may lower risk of colorectal cancer (5). More generally, flavonoid intake is associated with lower risk of esophageal adenocarcinoma (6,7) and breast cancer (8). These epidemiological patterns have been guided by in vitro mechanistic studies on immune function, cell proliferation and apoptosis (9,10).…”
Section: Introductionmentioning
confidence: 96%
“…In particular, flavonones associate with lower risk of esophageal squamous cell carcinoma (3), flavones and flavonols against renal cell carcinoma (4), and increased intakes of anthocyanadins, flavones, and flavonols may lower risk of colorectal cancer (5). More generally, flavonoid intake is associated with lower risk of esophageal adenocarcinoma (6,7) and breast cancer (8). These epidemiological patterns have been guided by in vitro mechanistic studies on immune function, cell proliferation and apoptosis (9,10).…”
Section: Introductionmentioning
confidence: 96%
“…Polyphenols have been documented as one of the major contributors to the antioxidant capacity of the American diet (14). Several studies have reported the intakes of phenolic compounds (13,15,16) and flavanoids (17)(18)(19)(20) and that about two-thirds of the total dietary polyphenols were flavonoids (14). Due to their ubiquity, PA account for a large fraction of the polyphenols consumed (21).…”
Section: Introductionmentioning
confidence: 98%
“…Flavonoid values were derived from 3 USDA databases on flavonoids (16), proanthocyanidins (17), and isoflavones (18) and other research publications (22)(23)(24), as described previously (25). For mixed dishes (eg, pizza, coleslaw), we assigned weighted content values based on recipes from standard cookbooks.…”
Section: Dietary Assessmentmentioning
confidence: 99%